Pyoderma Gangrenosum in a Splenectomy Incision in a Patient with Haemolytic Anaemia due to Hereditary Spherocytosis: a Case Report and Literature Review - Piotr K. Krajewski; Iwona Chlebicka; Jacek C. Szepietowski; Joanna Maj (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)